Data-Driven Approach to Understanding Complex Urban Phenomena: A Preliminary Study on the Gentrification of H Street NE in Washington, DC - Muieen Cader; Tsung-Wen Yen; Andrea Nanetti; Siew Ann Cheong (Urban Science)
Cities are increasingly recognized as complex systems, emerging through conditional and history-dependent urban processes. To understand a complex urban phenomenon to the point where we can act on it, we need a quantitative yet holistic approach. In this paper, we report on a preliminary study on the gentrification of H Street NE in Washington, DC, USA. Popular accounts claim that this started in 2016, with wealthier new residents displacing poorer old residents. When we examined a cross-section of demographic, income, housing, commercial activity, and social activity data, we found a classic gentrification sweeping over H Street NE starting around 2000. These slow changes drove rapid changes in renter proportions and rents in one of the five census tracts making up the community, a wave of church closures, and a sudden doubling of restaurants and nonclassified businesses. Our results suggest that the gentrification of H Street NE is a small messy piece in a broader picture of urban transformation in Washington, DC.